Konten Kisah Akun Instagram @perempuanberkisah Sebagai Ruang Bersuara Perempuan Korban Kekerasan Berbasis Gender Online - Sekar Diva Parasdya; Nuryanti Nuryanti; Mite Setiansah (Avant Garde, 2023)
Violence against women is increasing every year. One type of Gender-Based Violence (KBG) against women that will become a concern in 2021 is Online Gender-Based Violence (KBGO). In the current era of digitalization, where everything can be done easily using the internet, violence against women is easy to find. Regulations that have been issued as a legal umbrella, actually make it difficult for women as victims and think that this problem occurs because of women's mistakes. Victims of sexual violence do not report it because in reality, sexuality is still considered a taboo subject. The Instagram account @perempuanberkisah through one of its contents, namely story content, exists as a forum for women victims of violence to share their experiences. The content provides space for women who cannot talk about their experiences in other forums. This study aims to analyze how female victims of KBGO tell about the violence they experienced through story content on the Instagram account @perempuanberkisah. This study uses a descriptive qualitative approach. The data collection technique was carried out using the content analysis method on the research object, namely the story content of the Instagram account @perempuanberkisah. The data analysis method used is content analysis by Philipp Mayring. The results of this study are that the Instagram account @perempuanberkisah provides a safe space for female victims and survivors of KBGO. Through story content, women victims and survivors of KBGO can talk about the violence they experienced without fear of being judged.